Quasi-2D crystals as an electrode material for high energy storage devices - Lukiyanets, B.A.; Matulka, D.V. (Physics and Chemistry of Solid State, 2024)
The high value of the specific surface area in quasi-2D crystals, with the possibility of a large variation of their properties due to external factors, allows us to consider them as electrode materials for supercapacitors. In order to describe the specific physical properties of such crystals due to the different types of chemical bonds in them, a model is proposed. The electronic spectrum obtained has the structure (discrete levels) + (two-dimensional bands) or (mini-bands) + (two-dimensional bands). A significant relationship between the geometrical, spectral and statistical properties of the quasi-2D crystals has been found by studying the energy density of the accumulation W within the microscopic model. Contrary to existing models, the proposed model shows that under certain conditions there are two or more optimal crystal sizes where the experimentally observed maximum energy density W is realised. The model and its qualitative conclusions should be considered as the result of a microscopic approach to the problem.